Static and dynamic nonlinear response of masonry walls. (15th December 2018) - Gatta, Cristina; Addessi, Daniela; Vestroni, Fabrizio
Highlights: A damage-plastic model for nonlinear macromechanical analysis of masonry is proposed. The mesh-dependency problem is overcome by adopting a nonlocal regularization technique. A nonlinear FE procedure is developed based on a predictor-corrector algorithm. Model validation is performed by comparing numerical and experimental results on masonry panels subjected to cyclic loads. Effect of degrading mechanisms on dynamic response is analyzed through the frequency response curves of masonry elements. Abstract: A nonlocal damage-plastic model is proposed to investigate the mechanical response of masonry elements, under static and dynamic actions. The adopted constitutive relationship is able to capture degrading mechanisms due to propagation of microcracks and accumulation of irreversible strains. Moreover, the stiffness recovery, due to re-closure of tensile cracks when material undergoes compression strains, is taken into account to properly simulate the masonry cyclic response. The proposed relationship is implemented in a 2 D plane stress finite element and a predictor–corrector procedure is developed to solve the nonlinear evolution problem of damage and plastic variables. The model validation is carried out by comparing numerical and experimental results on masonry panels under cyclic quasi-static conditions. Then, to analyze the effect of the evolution of degrading mechanisms on masonry dynamic response, the frequency response curves of a slender wall are evaluated by highlighting the influence of the proposed masonry constitutive relationship with respect to other widely studied models characterized by nonlinear invariant restoring forces.